(3QSGdI aj MLjI GdTgQIs - (3GdWHGWHGFj, GdcGXej, GdMGFQj, GdCUHgGfj, Ydj Hf eMeO Ydj Hf CHj GdeYGdj, J (B1231 (3gs
(3ChdgG (B:s
(3GdMeO ddg (B.. (3gPg QSGdI eaQOI aj HjGf MLjI GdTgQI hLhGR GdGYJeGO YdjgG aj EPHGJ GdCMcGe GdTQYjI(B... (3ceG fHg Ydjg TjNfG GdTgjO GdKGfj QMeg Gddg aj cJGH GdQYGjI GdPj aj OQGjI GdMOjK (B.. (3hLgI ajeG Mcj Yfg ef Cf GcKQ GdabgGA GdPjf fTChG HYO GdTjN cGfhG jJHYhfg as
(3BNQgG (B:s
... (3hde GJMbbg CUdG HYO TgQI GdNdGa GdYXje aj MLjJgG abO GfcQgG ef eMbbj eJCNQj GdeJCNQjf LeGYI dG jecf GdGWdGY eYgG HGdELeGY ZGdHG SjeG (B...(3Je GdQSGdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\ 17s
(3GdPQjYI (B6\1479s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs